2018
DOI: 10.1016/j.drugalcdep.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Salience network coupling is linked to both tobacco smoking and symptoms of attention deficit hyperactivity disorder (ADHD)

Abstract: The greater ASRS scores in nicotine dependent individuals is in line with existent literature and the stronger dACC-AI coupling in smokers further supports the role of this network in nicotine dependence. The significant association between dACC-AI coupling and ASRS suggests that intra-SN coupling strength may impact neurocognitive functioning associated with both ADHD symptoms and nicotine dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…Uniquely predictive connections were found for ADHD and depression symptom domains. Consistent with findings of altered function in the anterior insula (59,84,85) and abnormally-enhanced connectivity within cingulo-opercular and/or salience networks in individuals with ADHD (86)(87)(88), developmentally-accelerated connectivity in several middle and anterior dorsal insula regions was associated with greater ADHD symptom severity. Developmentally-delayed connectivity with nearby bilateral inferior frontal gyrus (BA 45), on the other hand, was associated with greater ADHD symptom severity, consistent with the well-established role of this region in inhibitory control dysfunction in ADHD (29,59), and its upregulation with stimulant medication (89).…”
Section: Maturation Of Striatal Connectionssupporting
confidence: 71%
“…Uniquely predictive connections were found for ADHD and depression symptom domains. Consistent with findings of altered function in the anterior insula (59,84,85) and abnormally-enhanced connectivity within cingulo-opercular and/or salience networks in individuals with ADHD (86)(87)(88), developmentally-accelerated connectivity in several middle and anterior dorsal insula regions was associated with greater ADHD symptom severity. Developmentally-delayed connectivity with nearby bilateral inferior frontal gyrus (BA 45), on the other hand, was associated with greater ADHD symptom severity, consistent with the well-established role of this region in inhibitory control dysfunction in ADHD (29,59), and its upregulation with stimulant medication (89).…”
Section: Maturation Of Striatal Connectionssupporting
confidence: 71%
“…Interestingly, a stronger dysregulation was observed in the AUD + ADHD group also compared to AUD and ADHD regarding the SN. A dysregulation of the SN was reported previously as a link between ADHD and tobacco smoking (Janes et al, 2018). Even though causal interpretations still lack supporting data it, one might hypothesize that a dysregulation of the SN in ADHD may be considered as a risk factor for developing SUD.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, a stronger dysregulation was observed in the AUD + ADHD group also compared to AUD and ADHD regarding the SN. A dysregulation of the SN was reported previously as a link between ADHD and tobacco smoking (Janes et al, 2018).…”
Section: F I G U R Ementioning
confidence: 71%
See 1 more Smart Citation
“…There are many questions concerning nicotine’s role in socially relevant outcomes that neuroimaging is well suited to address. As just a few examples, a recent fMRI study found that smokers have enhanced salience network coupling compared with nonsmokers (Janes et al, 2018). Because the salience network is thought to inform a person’s behavior by integrating internal and external information, this line of research could be extended to evaluate how nicotine influences attention to salient social stimuli.…”
Section: Discussionmentioning
confidence: 99%